Scientific Representations at the UPR School of Tropical Medicine. IV: Special Technical Studies - Mayo-Santana, Raúl (Puerto Rico Health Sciences Journal, 2020)
The essay examines the scientific representations that unfolded and evolved at the University of Puerto Rico School of Tropical Medicine (STM) under the auspices of Columbia University (1926-1949). This article on the STM’s scientific endeavors is the fourth in a historical serial collection about the images and evolution of sciences at the institution and it portrays the diagrammatic representations of special technical research aspects and studies (i.e., personnel, epidemiology, methodology, animal studies, biology, field studies, treatment and immunology, and chemotherapy agents). The essay focuses on the emerged scientific representations and on the nature and evolution of sciences at the School, and has been divided into four sections: a) images of science, b) evolution during the first two eras, c) the third and last era unfolding, and d) special technical studies. In this paper the scientific representations have been brought about mainly through the analyses of research publications in external and local venues. The analysis of the STM’s scientific evolution has been organized in three distinct historical stages: 1926-31, 1932-40, and 1941-49. These representations open an exploration pathway for a better understanding of the intricate interrelationships between the techné and the episteme horizons of tropical medical science in Puerto Rico.